STUDI EKSISTENSI HUKUM ISLAM PADA PERATURAN DAERAH DI SULAWESI SELATAN - Ariesman, Ariesman; Iskandar, Iskandar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
Islamic law existed in Indonesia in the 7th century AD or the first century Hijri. This is in line with the entry and development of Islam in Indonesia, whereas previously Indonesians embraced animism, dynamism and Hindu-Buddhist beliefs which were very far from Islamic values. The development of Islamic Law in Indonesia continues to experience development in all regions in the archipelago, including has spread in South Sulawesi, so that the values ??or rules of Islam have colored all aspects of community life in South Sulawesi. Based on the results of the literature study, the development of Islamic law in South Sulawesi began since Islam was officially accepted by King Gowa-Tallo on Friday night, September 22, 1605 AD The first king to accept Islam on that day was a king from Tallo named I Malingkaang Daeng Mannyonri , the king then changed his name to Sultan Abdullah Awwalul Islam. In line with the long course of time the development of Islamic law is increasingly showing its existence through the birth of the "Islamic Sharia Enforcement Preparation Committee" (KPPSI) which was inaugurated on April 15, 2001 AD at the al-Markaz al-Islami Mosque in Makassar and various official regulations issued by the provincial, district and village level governments.